HYDROCHEMICAL MODELLING FOR PRELIMINARY ASSESSMENT OF MINEWATER POLLUTION - Banwart S.A.; Malmstrom M.E. (My University, 2001)
A conceptual model for preliminary assessment of minewater pollution within the risk-based corrective action (RBCA) framework for environmental management is developed. The model aims to assist classification of a site regarding the potential threat to the environment and help assess whether the assumptions used in this classification are appropriate. The model estimates contamination source strength, longevity and possible future changes in discharge quality and can be applied with sparse data sets. The model relates solute export in the discharge to source minerals which includes sulphide phases that produce acidity and metals contamination and carbonate and aluminosilicate phases which provide natural attenuation to neutralise acidity and immobilise metals.We present and apply limited data from three sites representing a mine rock waste deposit located above the water table, a flooded abandoned coal mine with deep workings and a mine tailings deposit. Results from the rock waste deposit indicate that calcite no longer provides significant attenuation of the present acidity load and that acid generation and associated loads of Cu2+ may persist for a period of up to two centuries. The abandoned coal mine has a discharge that is presently alkaline, with calcite depletion expected to occur before pyrite is consumed, possibly yielding a future drop in pH. The lifetime for these minerals is similar at this site, and on the order of several centuries, thus rendering the estimate of future water quality evolution very uncertain. The mill tailings deposit is expected to produce acidic discharge on a time scale of one century. However, conclusive quantification of calcite weathering was not possible, leaving open the possibility that the weathering of Mg-silicate minerals provides important attenuation of the present acidity load.
Keywords: HYDROCHEMICAL MODELLING; MINEWATER; POLLUTION; RISK ASSESSMENT